A Study to Evaluate the Impact of Nurse-led Intervention on Competency Level Regarding Care of Patients on Mechanical Ventilators Among ICU Nurses Working in Selected ICUs at Pt. Bd Sharma PGIMS Rohtak - Shashi Kant; Kavita Choudhary; Dhruva Choudhary (International Journal of Emergency and Trauma Nursing and Practices, 2024)
Introduction: The nurse caring for mechanically ventilated patients must be skilled and possess a deep understanding, along with specialized knowledge, of mechanical ventilators (MV). This study is intended to evaluate the impact of nurse-led intervention on competency levels regarding the care of patients on MV among ICU nurses. Objective: To assess the pre- and post-test knowledge, practices, and attitudes of ICU nurses, evaluate the effectiveness of nurse-led interventions on the competency levels of ICU nurses, determine the correlation between pre-test knowledge, practices, and attitudes, and examine the relationship between pre-test scores on knowledge, practices, and attitudes with selected demographic variables. Methods: This study used a quantitative approach based on a pre-experimental design, specifically applying a one-group pre-test and post-test model. The study recruited 80 ICU nurses from ICUs of PGIMS Rohtak by using non-probability convenience sampling technique. For data collection, structured knowledge questionnaire was used for assessment of knowledge level, checklist for practice level and attitude scale for assessment of attitude. The data were analyzed using both descriptive and inferential statistical techniques. Result: Nurse-led intervention significantly increased nurse’s competency level, which includes knowledge level (value of t= 26.184 and p value = .000), nurse’s practice level (value of t= 20.757 and p value = .000), and nurse’s attitude (value of t= 11.175 and p value = .000). The competency level of nurses regarding care of patient on mechanical ventilators was significantly associated with their professional qualifications, number of years of experience and nurse having in service education. Conclusion: The analysis showed significant increase in the competency level of ICU nurses. A notable positive correlation was found between knowledge and practice, as well as between knowledge and attitude. There is a need for intermittent continuing education programs to increase the competency level of nurses.
Keywords: ICU; competency; mechanical ventilator; nurse-led intervention; nurses